Climate exerts a greater modulating effect on the phytoplankton community after 2007 in eutrophic Lake Taihu, China: Evidence from 25 years of recordings. (October 2019) - Guo, Chaoxuan; Zhu, Guangwei; Qin, Boqiang; Zhang, Yunlin; Zhu, Mengyuan; Xu, Hai; Chen, Yuwei; Paerl, Hans W.
Highlights: Nutrients cause changes in the phytoplankton community during early eutrophic periods. Climate plays a greater modulating role in community variation under nutrient regulation conditions. Rising air temperatures and greater light availability have led to a recent sharp increase in the phytoplankton biomass. The seasonal biomass usually peaks in summer, and other patterns are observed in winter and autumn. Abstract: Long-term phytoplankton community changes indicate the trophic status under nutrient regulation conditions in eutrophic lakes, although the modulatory role of climate change scenarios in their indicative function has been underestimated. Hence, we analyzed the relative contributions of nutrient and climate factors to interannual and seasonal variations in the phytoplankton biomass and composition from 1992 to 2017 in Meiliang Bay, Lake Taihu, China. Discrete phytoplankton communities from five periods were classified according to their interannual features. Variations in the phytoplankton community composition were observed during the five periods, and these variations included a shift from exclusive cyanobacterial dominance before 2008 to diatom-cyanobacterial codominance in 2008–2010 and from cyanobacterial dominance in 2011–2014 to cyanobacterial-diatom codominance in 2015–2017. The phytoplankton biomass pattern typically peaked in summer, although peaks also occurred in winter 2008–2010 and autumn 2011–2014. Additionally, the phytoplankton biomass increased by threefold from 2015 to 2017, which might have been related to rising air temperatures and greater light availability. The variance in the phytoplankton community was significantly explained by nutrient (ammonium, nitrate and phosphate) and climatic (air temperature and wind speed) factors. However, the explaining effect of the factors varied among the five periods: nutrients strongly impacted the community composition from 1992 to 2007, whereas climatic variables became more important modulators after 2007. These results reveal that climatic factors play importance roles in shaping the phytoplankton community and cyanobacterial blooms and suggest that differences in the roles between specific climatic conditions should be considered. Future declines in cyanobacterial blooms require further dual nitrogen and phosphorus reduction and longer recovery times under current climate change scenarios in this and possibly other shallow eutrophic lakes.